2017
DOI: 10.1039/c7dt00529f
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic coatings for the protection of upconverting nanoparticles against dissolution in aqueous media

Abstract: Upconverting nanoparticles (UCNPs) of β-NaYF, co-doped with Yb and Tm and 21-36 nm large, were synthesized using a modified thermal decomposition method. The as-synthesized UCNPs were coated with oleic acid and dispersed in nonpolar media. Their morphology, size and crystal structure were analysed with transmission electron microscopy and X-ray diffraction. The UCNPs showed a fluorescence emission spectrum characteristic of Tm. Their dissolution in water (pH ∼ 4-5) and phosphate buffered saline (PBS, pH = 7.4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…Recently, an amphiphilic coating was demonstrated to be successful in hindering the disintegration and thus shielding the particles’ luminescence from quenching. 26 Preventing the disintegration of the materials is vital, not only because of the optical changes harming the reproducibility of the measurements 20 , 21 but also to prevent the leaking of lanthanide and fluoride ions into the tissue or living cells in biomedical imaging. 27 , 28 This means that development of new surface modifications and methods to effectively stop the disintegration are increasingly important topics in the research of upconverting nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an amphiphilic coating was demonstrated to be successful in hindering the disintegration and thus shielding the particles’ luminescence from quenching. 26 Preventing the disintegration of the materials is vital, not only because of the optical changes harming the reproducibility of the measurements 20 , 21 but also to prevent the leaking of lanthanide and fluoride ions into the tissue or living cells in biomedical imaging. 27 , 28 This means that development of new surface modifications and methods to effectively stop the disintegration are increasingly important topics in the research of upconverting nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory classical analytics used for determining the composition of bulk material of synthesised compounds containing fluorine 118,[276][277][278][279][280][281][282][283] was extended to thermochemical investigations, 118,140,141,[280][281][282][284][285][286][287] measurement uncertainty evaluation, 171 determination of fluorine in food 149,183 and environmental samples 7,288,289 and nanomaterials. [290][291][292][293][294] Principles of thermochemistry were used for the estimation of the entropies of formation of fluorine containing aqueous anions 285 and to discuss ions containing solely fluorine atoms 286 and oxidation potential of fluorine. 287 Possible reactions proceeding during total decomposition of fluorine containing materials by pyrohydrolysis, oxygen bomb combustion and alkaline carbonate fusion were suggested and accompanying thermochemistry discussed.…”
Section: Our Research and Future Directionsmentioning
confidence: 99%
“…We also participated in characterization of upconverting, lanthanide-doped, fluoride nanoparticles, which show a great potential in bioimaging. [290][291][292][293][294] Fluorine research remains relatively sporadic also because of a lack of sound analytical techniques enabling fast and multielemental analysis of F. Thus the predominate method for F analysis remains fluoride ion selective electrode.…”
Section: Our Research and Future Directionsmentioning
confidence: 99%
“…8 However, the luminescence intensity of these Fe 3 O 4 @Mn 2+ -doped NaYF 4 :Yb/Er NPs in water was signicantly reduced compared to the original hydrophobic NPs when using a ligand exchange method, the quenching effect is mainly caused by the nonradiative decay of the electronically excited states of the dopant lanthanide ions caused by surface ligands and water molecules. 8,40,41 It was found that compared with the ligand exchange method, the amphiphilic polymer coating method can maintain better UCL intensity ascribed to the presence of hydrophobic OA ligands in the later case, which could hinder at least partly the direct access of water molecules to the particle surface. 40 …”
Section: -27mentioning
confidence: 99%
“…8,40,41 It was found that compared with the ligand exchange method, the amphiphilic polymer coating method can maintain better UCL intensity ascribed to the presence of hydrophobic OA ligands in the later case, which could hinder at least partly the direct access of water molecules to the particle surface. 40 …”
Section: -27mentioning
confidence: 99%